The effect of hearing impairment and social participation on depressive symptoms in older adults: a cross-lagged analysis - Zhao, Hejun; Wang, Xinying; Shi, Yuhao (Frontiers in Computational Neuroscience, 2023)
Objective: This study aimed to investigate the relationship between hearing impairment, depressive symptoms, and social participation in older adults. Methods: The study used data from the China Health and Retirement Longitudinal Study (CHARLS) in 2013 and 2018, which included 3,980 samples. The analysis was conducted using cross-lagged structural equation modeling with SPSS 23.0 and Mplus 7.4. Results: The findings show that from 2013 to 2018, older people had significantly more hearing impairment and depressive symptoms and significantly less social participation. Hearing impairment was a significant negative predictor of social participation, and older adults with hearing impairment were less likely to participate in social activities. In addition, there may be a bidirectional relationship between hearing impairment and depressive symptoms, with both being positive predictors of each other. Finally, the study found that social participation played an important mediating role in the relationship between hearing impairment and depressive symptoms. Conclusion: The study's findings highlight the complex interplay between hearing impairment, social participation, and depressive symptoms in older adults. Therefore, it is important to intervene promptly when hearing impairment is detected in the elderly; pay attention to patient guidance and comfort for the elderly with hearing impairment, give them positive psychological support, encourage them to get out of the house and participate in more social activities to avoid depressive symptoms.The study's results may inform the development of targeted interventions to address the mental health needs of older adults with hearing impairment.